Dharmagita and Character Education: An Ethnographic Perspective on Literary Traditions among Ubud Youth - Parmini, Ni Putu; Wardhani, Ni Ketut Srie Kusuma (Journal of Ecohumanism, 2025)
This ethnographic study examines the influence of Dharmagita, a traditional Balinese literary form, on character education among youth in Ubud. Data were collected through in-depth interviews, participant observations, and analysis of Dharmagita texts, engaging 30 Balinese youths aged 15-21. The study employs semiotic analysis to decode the symbolic representations within the texts and psychoanalytic theory to explore their impact on the psychological development of moral values. The findings highlight Dharmagita’s role in embedding values such as care, fairness, honesty, forgiveness, cooperation, responsibility, and community awareness into the fabric of youth education. Integrating these values into everyday life through literary traditions provides a dual benefit: moral development and cultural continuity. Additionally, the study notes Dharmagita's entertaining elements enhance its receptivity among youth, suggesting its potential as an accessible tool for moral instruction. Limitations regarding the diverse interpretations of Dharmagita and its applicability across different educational settings are discussed. This research contributes to the dialogue on culturally responsive pedagogy, offering Dharmagita as a model for integrating indigenous literary practices into character education frameworks.